Mini-Mental State Examination to Assess Cognitive Function in Elderly - Dafinta Widia Komala; Dwi Novitasari; Rosi Kurnia Sugiharti; Sidik Awaludin (Jurnal Keperawatan Malang, 2021)
Background: With increasing age, it will cause a decrease in the function of body systems, one of which is a decrease in cognitive function. Impaired cognitive function in the elderly can be in the form of language disorders, loss of short and long-term memory, and disorientation of time and place. Based on the results of a pre-survey conducted at Rojin Home Itoman Teinsagu No Ie Japan, it was found that 35 elderly and 18 elderly suffered from dementia. Purpose: This study was aimed to describe the cognitive function of the elderly at the Rojin Itoman Teinsagu No Ie House in Japan using the Mini-Mental State Examination instrument. Methods: This research uses descriptive quantitative research methods. The sampling technique used in this research is the total sampling technique. There were 33 elderly as respondents. Results: The results showed that most of the respondents in the elderly category (75-90 years) were 24 respondents (72.7%), the dominant female respondents were 21 respondents (63.6%) with most of them experiencing a moderate decline in cognitive function 19 respondents (57.6%). All 33 respondents (100%) were correct on the word repetition command, a total of 29 (87.9%) respondents were correct on the command to close their eyes. This means that the cognitive function of the elderly is good in language repetition and comprehension. But, as many as 20 (60.6%) respondents got a score of 0 on the attention/concentration. Conclusion: Impaired cognitive function of the elderly is the biggest cause of dependence on others to care for themselves due to the inability to carry out daily activities. Nurses can assess it using the MMSE so that the elderly receive therapy immediately. Key words: cognitive function; dementia; elderly; MMSE.